Perfil do idoso acusado de cometer crime em um município do litoral Norte do Rio Grande do Sul - Brandão, Sérgio Vieira (2015)
Despite the remarkable growth of the elderly population, and the growing concern from various arenas with this population segment, old age is likewise the outcome of diverse opinions, myths and prejudices. It is genuine that the elderly frequently are victims of several kinds of hostility, but the fact remains that he or she, too, is also an agent of the committal of criminal offenses. In order to try to understand this phenomenon, I tried to describe the profile of the elderly accused of committing crime. Through documentary research could show that among the 4806 surveyed occurrences - corresponding to the total Occurrences bulletins registered in Imbé-RS Police Station in 2013 - found 92 occurrences related to elderly offenders (1.91% of total occurrences). The total population is 17,670 inhabitants (IBGE, 2010), and 2803 are elderly (15.9% of total population). The elderly population is formed by 1458 women (52% of the elderly) and 1345 men (48% of the elderly). Thus, we can say that in the period surveyed, 3.28% of the elderly were accused of committing some sort of crime. The proportion of non-aged adults (18 to 59 years) and seniors (60 and over) is 3.43 non-elderly adults for every elderly, i.e., older represent 22.6% of adults and 15.9% of the entire population. This study was able to show the profile of the elderly accused of committing crime: 75% are men; 53.2% have primary education and only 4.4% of them are illiterate. Therefore, a continuous and integrated action of the health network and public safety with other social areas – particularly social studies – can anticipate risk situations for the elderly (and the whole community) as well as preventing harmful occurrences, implementing studies and anticipating interventions to prevent injuries diseases, to promote citizenship, sort out conflicts and reduce urban violence.